Não fechem minha escola: urbanização e gestão da escola contra o vivido, uma análise sobre a "reorganização" de 2015 - Silva, Michael Cristtofer da (Universidade Federal de São Carlos, 2019)
The objective of this study is to understand how the school reform project “Reorganization” of 2015 reproduces socio-spatial inequality in Sorocaba-SP, more specifically around a school in the outskirts of the city. With this initial objective in mind, we have made a diagnosis based on the relationship between school management and urbanization. The research cut took into account Henri Lefebvre´s theory of space production and had the contribution of the most diverse authors from the most varied areas of the Social Sciences to the accomplishment of a robust analysis of the events in that period. The historical recovery of the constitution of schooling and urbanization was important for the formulation of genetic movements that culminated in the occupation of school project that produced and reproduces the current reforms. We understand that this whole process is part of a totalization in the space convergence of the school bureaucracy to the founding elements of urbanization, which reveals the modus operandi expressed in modernity, its unfinished “emancipatory project”. The results of the survey show Sorocaba that pushes public education apparatus into regions of social vulnerability, or that produces “sanitized islands”, closing schools in its expanded center. The “Veiled Reorganization” occurs discreetly and areas of real estate speculation are amortized, in a attempt of property valuation. A school in the northwest of the city was used as the locus of the study, and the concreteness of the main concepts: democratic management; urbanization and the world of life are exposed throughout the text as way of expressing the vicissitudes of the real, but not imposing the phenomenon in a finished form, emphasizing its contribution as a way of understanding that is always constant, and never closed.
Don't close my school: urbanization and school management against the lived, an analysis of the "reorganization" of 2015
Keywords: Reorganização; CIENCIAS HUMANAS::GEOGRAFIA